Hermann Swoboda papers - Swoboda, Hermann, 1873-1962.
Legal briefs by Swoboda and his attorneys relating to a lawsuit filed by Swoboda against Wilhelm Fliess and Richard Pfennig over a plagiarism controversy. Includes a draft of an article by Swoboda on genius and heredity.
Psychologist.
In German.
Forms part of: Sigmund Freud collection.
Keywords: Fliess, Wilhelm, -- 1858-1928.; Pfennig, Richard; Genius; Heredity; Plagiarism; Psychologists